English Club to Improve Students’ Speaking Skills: A Case Study of an Indonesian Islamic Senior High School - Desmiyanti (Universitas Adiwangsa Jambi, 2022)
This research aimed to investigate the role of English Club toward successful students. This was qualitative research in the form of a case study. It took place at an Islamic Senior High School in Sungai Penuh, Jambi Province, Indonesia. It involved 4 participants: 1 teacher and 3 students. It employed an interview, observation checklist, and audiovisual recording. The findings of this research revealed that: first, the students did not maximize their chances to speak English. It was caused by the function of English Club itself which was a preparation to face debate and speech competition. However, the students got their self-confidence and speaking skills: vocabulary and fluency. Second, the teacher applied a student-centered approach. In content selection, she selected content related to national values, students’ experiences, and appropriate to the level of learning. But, she ignored local values. In teaching, she used six strategies: setting goals, providing tasks that stimulate thinking, giving responsibility, working in a group, managing time in flexible ways, and refined understanding by using critical thinking. In helping to speak English, she polished and corrected students’ language. Further, she applied peer learning. Third, the learning environments in English Club were good enough. But, cultivating responsibility in the learner was not catered. Based on the findings, it can be concluded that the role of English Club was preparation to face competitions however it also improved the students’ speaking skills which increased their vocabulary, self-confidence, and fluency.